Antibacterial and Antifungal Activities of the Leaf Extracts of Mentha piperita L. (Majalah Kedokteran Bandung, 2026)
Herbal medicines are increasingly used due to the presence of bioactive compounds with antibacterial and antifungal properties. This study aimed to evaluate the antibacterial and antifungal effects of Mentha piperita L. extract against Porphyromonas gingivalis and Candida albicans. A laboratory-based experimental study with a post-test only control group design was conducted. The test organisms were exposed to M. piperita L. extract at concentrations of 3.125%, 6.25%, 12.5%, 25%, 50%, and 100%. The antibacterial and antifungal activities were evaluated using the agar well diffusion method to determine inhibition zones, followed by broth dilution tests to identify the Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC), and Minimum Fungicidal Concentration (MFC). Statistical analysis was performed using one-way ANOVA with a significance level of p
Keywords: Antibacterial; Antifungal; Candida albicans; Mentha piperita L.; Porphyromonas gingivalis